Clinically Acceptable Optimized Dose Reduction in Computed Tomographic Imaging of Necrotizing Pancreatitis Using a Noise Addition Software Tool. Issue 2 (March 2018) - Jaffe, Tracy A.; Tian, Xiaoyu; Bashir, Mustafa R.; Marin, Daniele; Patel, Bhavik N.; Ho, Lisa M.; Samei, Ehsan
Abstract : Objective: This study aimed to determine potential radiation dose reduction of contrast-enhanced computed tomography (CECT) for imaging necrotizing pancreatitis (NP) using a noise addition tool. Methods: Eighty-four patients were identified with at least 1 abdominopelvic CECT for NP within a 2-year period. Sixty consecutive scans were selected as reference radiation dose data sets. A noise addition software was used to simulate 4 data sets of increased noise. Readers rated confidence for identifying (i) anatomic structures, (ii) complications of NP, and (iii) diagnostic acceptability. Noise and dose levels were identified at acceptability threshold where observer scores were statistically indistinguishable from full-dose computed tomographies. Results: Observers' perception of image tasks decreased progressively with increasing noise ( P < 0.05). Acceptability and statistical analysis indicated that noise can be increased from 10 to 25 HU corresponding to an 84% reduction in dose without change in observer perception ( P < 0.05). Conclusions: Higher image noise levels may be tolerated in CECT in patients with NP.